Empowering Sudanese Women and Promoting Their Health and Well-Being: The Courage and Commitment of One Woman. Issue 5 (September 2015) - Callister, Lynn Clark
Abstract : Individual efforts of courageous women in under-resourced countries are making a difference to move forward in achieving the Millennium Development Goals.